Thick Filament Mechano-Sensing in Skeletal and Cardiac Muscles: A Common Mechanism Able to Adapt the Energetic Cost of the Contraction to the Task - Piazzesi, Gabriella; Caremani, Marco; Linari, Marco; Reconditi, Massimo; Lombardi, Vincenzo (Frontiers in Physiology, 2018)
A dual regulation of contraction operates in both skeletal and cardiac muscles. The first mechanism, based on Ca2+-dependent structural changes of the regulatory proteins in the thin filament, makes the actin sites available for binding of the myosin motors. The second recruits the myosin heads from the OFF state, in which they are unable to split ATP and bind to actin, in relation to the force during contraction. Comparison of the relevant X-ray diffraction signals marking the state of the thick filament demonstrates that the force feedback that controls the regulatory state of the thick filament works in the same way in skeletal as in cardiac muscles: even if in an isometric tetanus of skeletal muscle force is under the control of the firing frequency of the motor unit, while in a heartbeat force is controlled by the afterload, the stress-sensor switching the motors ON plays the same role in adapting the energetic cost of the contraction to the force. A new aspect of the Frank-Starling law of the heart emerges: independent of the diastolic filling of the ventricle, the number of myosin motors switched ON during systole, and thus the energetic cost of contraction, are tuned to the arterial pressure. Deterioration of the thick-filament regulation mechanism may explain the hyper-contractility related to hypertrophic cardiomyopathy, an inherited heart disease that in 40% of cases is due to mutations in cardiac myosin.